Meta Analisis : Pengaruh Model Guided Discovery Learning (GDL) terhadap Kemampuan Berpikir Kritis Siswa SMA - Lara Eliza Firma; Ganda Hijrah Selaras (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The Guided Discovery Learning (GDL) model is an educational method designed to cultivate students’ critical thinking through a guided exploration process. This study aims to investigate how the GDL model influences the critical thinking development of high school students. The research method employed is a literature review, involving an analysis of five relevant scholarly articles focusing on GDL implementation in learning environments. The results demonstrate that the GDL approach effectively enhances students’ ability to think critically—particularly in evaluating problems, analyzing data, and drawing reasoned conclusions. Furthermore, students involved in GDL-based instruction tend to be more engaged, capable of constructing hypotheses, and able to carry out simple investigative tasks. These improvements contribute not only to better academic results but also to the growth of reflective and analytical thinking, which are essential competencies in today’s digital era. Based on the findings, the GDL model is highly recommended as a teaching strategy that supports the advancement of students' critical thinking abilities within the school setting.